External validation of the ORBI risk score for cardiogenic shock prediction in patients with ST-segment elevation myocardial infarction. (3rd May 2023) - Riche, M; Verdaguer, J; Denisi, N; Biendel, C; Lhermusier, T; Roncalli, J; Volle, K; Carrie, D; Elbaz, M; Bouisset, F; Delmas, C
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Cardiogenic shock (CS) complicates 5 to 15 % of ST-segment elevation myocardial infarction (STEMI) cases. With a high-short term fatality rate estimated between 40 to 50 %, it is considered as the first cause of mortality in myocardial infarction. Early detection of patients in the state of "pre-CS" may improve prognosis as it makes it possible to adapt the monitoring and to establish an appropriate treatment at an earlier stage. The ORBI risk score (ORS) based on 11 variables was created in order to identify patients at high-risk of in-hospital STEMI-related CS but external validation is lacking. Aim: The primary objective of this study was to evaluate the external validity of the ORBI Risk Score in a Tertiary Hospital Centre in southern France. Methods: Consecutive STEMI patients managed by primary percutaneous coronary intervention (< 24 h after chest-pain onset) at our tertiary hospital in 2019 were retrospectively included. Patients with CS at admission, with previous fibrinolysis or without attempted p-PCI were excluded. Data necessary for the calculation of the ORBI risk score were collected (age, prior stroke/transient ischaemic attack, cardiac arrest upon admission, type of STEMI, first medical contact-to-pPCI delay, initial clinical presentation (Killip class, heart rate, blood pressure, glycaemia, culprit lesion, and post-pPCI TIMI-flow grade and the occurrence of in-hospital CS). The score's calibration was assessed by a graphical method and its discriminatory performance by calculating the C-statistic (ROC curve). Results: 287 patients were included (mean age 64 y.o, 81.2% male, anterior STEMI 40.8%, LAD culprit lesion 47%, median first medical contact-to-PCI delay 112 min). In-hospital CS occurred in 18 patients (6.3%) with all-cause in-hospital mortality of 4.2%. The observed in-hospital CS rates were respectively 1.8%, 2.9%, 41.7%, and 50 % in the four risk categories, ranging from low ( ORS 0–7) to low- to-intermediate (ORS 8–10), and from intermediate-to-high (ORS 11–12) to high (ORS≥13). The score showed satisfactory discrimination (c-statistic of 0.90 (CI 95% 0.83–0.97), p<0.001) with 93 % correctly classified patients at a cut-off ≥ 10. However, in term of calibration, the score tends to under-estimate the occurrence of CS, mostly in high-risk patients. Conclusion: The ORBI risk score demonstrated good discrimination, but it lacked calibration in the case of this validation cohort. Notwithstanding this drawback, it may facilitate the identification of STEMI patients at high risk of CS and thus increase their enrolment in CS dedicated clinical trials. Further validation studies are needed before scaling up its routinely clinical use. Discimination : ROC curve Calibration graph in validation cohort